Buckling/post-buckling strength of friction stir welded aircraft stiffened panels. (February 2014) - Murphy, A; Ekmekyapar, T; Özakça, M; Poston, K; Moore, G; Elliott, M
Assembling aircraft stiffened panels using friction stir welding offers potential to reduce fabrication time in comparison to current mechanical fastener assembly, making it economically feasible to select structurally desirable stiffener pitching and novel panel configurations. With such a departure from the traditional fabrication process, much research has been conducted on producing strong reliable welds, with less examination of the impact of welding process residual effects on panel structural behaviour and the development of appropriate design methods. This article significantly expands the available panel level compressive strength knowledge, demonstrating the strength potential of a welded aircraft panel with multiple lateral and longitudinal stiffener bays. An accompanying computational study has determined the most significant process residual effects that influence panel strength and the potential extent of panel degradation. The experimental results have also been used to validate a previously published design method, suggesting accurate predictions can be made if the conventional aerospace design methods are modified to acknowledge the welding altered panel properties.